2017
DOI: 10.18632/oncotarget.17740
|View full text |Cite
|
Sign up to set email alerts
|

TUBB3 overexpression has a negligible effect on the sensitivity to taxol in cultured cell lines

Abstract: Microtubules are cellular targets for a variety of anticancer therapies because of their critical function in mitosis. Taxol belongs to a class of microtubule targeting agents that suppresses microtubule dynamics and interferes with the functioning of the mitotic spindle, thereby effectively blocking cell cycle progression of rapidly proliferating tumor cells. Despite its antitumor activity, drug resistance remains a common obstacle in improving its overall clinical efficacy. Previous studies have shown that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 42 publications
1
20
0
2
Order By: Relevance
“…To extend this analysis to a larger number of genes, we switched to a more flexible gene activation system that does not require a custom-made TALE for every promoter of interest. We chose a previously established human RPE-1 cell line that stably expresses the SunCas-CRISPRa system (Tame et al, 2017; Tanenbaum et al, 2014), in which multiple copies of VP64 can be targeted to a promoter of interest by a single sgRNA. We first used this system to activate NLGN1 , a gene of 885 kb that is located in a LAD.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To extend this analysis to a larger number of genes, we switched to a more flexible gene activation system that does not require a custom-made TALE for every promoter of interest. We chose a previously established human RPE-1 cell line that stably expresses the SunCas-CRISPRa system (Tame et al, 2017; Tanenbaum et al, 2014), in which multiple copies of VP64 can be targeted to a promoter of interest by a single sgRNA. We first used this system to activate NLGN1 , a gene of 885 kb that is located in a LAD.…”
Section: Resultsmentioning
confidence: 99%
“…The RPE-1 cell line stably expressing SunTag-CRISPRa (Tame et al, 2017) was kindly provided by the R. Medema lab (Netherlands Cancer Institute, Amsterdam) and cultured in DMEM-F12 supplemented with 10% FCS. F121-9 mES cells were kindly provided by J. Gribnau (Erasmus Medical Center, Rotterdam, the Netherlands) and cultured in feeder-free 2i medium according to the 4DNucleome protocol (https://data.4dnucleome.org/protocols/cb03c0c6-4ba6-4bbe-9210-c430ee4fdb2c/).…”
Section: Methodsmentioning
confidence: 99%
“…Even more problematic, in BC [ 55 ], clear cell ovarian carcinoma [ 56 ] and melanoma [ 57 ], studies have reported that high expression of βIII-tubulin was linked to sensitivity to taxane-based chemotherapy and not resistance. A very recent report indicated that βIII-tubulin overexpression has a negligible effect on the sensitivity to taxol in cultured cell lines [ 58 ]. We have also shown that in MCF-7 cells selected for taxol resistance, the expression level of βIII-tubulin is not elevated but decreased [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Even more problematic, high expression of βIII-tubulin was found associated with sensitivity to taxane-based chemotherapy and not resistance in BC [ 42 , 55 ], clear cell ovarian carcinoma [ 56 ] and melanoma [ 57 ]. A very recent report showed that βIII-tubulin overexpression has a negligible effect on the sensitivity to taxol in cultured cell lines [ 58 ]. We have also shown that in MCF-7 cells selected for taxol resistance, the expression level of βIII-tubulin is not elevated but decreased and βII- and βIV-tubulin levels are increased [ 42 ].…”
Section: Introductionmentioning
confidence: 99%
“…These antimitotic agents stimulate the polymerization of the microtubules. This site-specific binding seems to antagonize the breakdown of this cytoskeletal key protein, with consequent formation of stable and abnormal microtubules, blocking the progression of G2 and M phase in the cell cycle [ 68 – 70 ].…”
Section: Discussionmentioning
confidence: 99%